Pemberdayaan Komunitas P2WKSS untuk Mengendalikan Stunting di Kabupaten Ciamis - Susan Sintia Ramdhani; Adi Nurapandi; Yuyun Rahayu; Restika Puspa Ningtias; Alis Sundewi; Nabil Ridla Firdaus (Yayasan Inspirasi El Burhani, 2022)
Introduction: Stunting is a condition in which a child has an unbalanced height ratio for his age, occurs due to lack of nutrition so that the child’s growth is stunted. One of causes of stunting in infants and toodlers is the lack of parental knowledge about stunting. Objective: This community service activity is carried out by empowering the community regarding stunting which is expected after this program is carried out, the community and parent know about stunting control and pay more attention to the growth of infants and toodlers. Method: This activity is carried out by providing counseling through 4 stages, namely interviews, providing education about stunting, then monitoring for 21 days and evaluating. Result: Of the 48 respondents before the counseling, who knew about stunting only 20 people (41,6%) after the parental knowledge counselimg increased to 40 people (83,3%). Results of monitoring for 21 days, parents are able to apply the understanding gained by providing good nutritional intake and paying attention to hygiene in infants and toodlers. Conclusion: This service activity succeeded in increasing the knowledge of parent about stunting so that they really play a role as the main guide for the growth and development of infants and toodlers by paying more attention to the nutritional needs and development of children.